THE BUG ENCYCLOPEDIA - Marquardt, Meg (Minneapolis, Minnesota : Abdo Reference, an imprint of Abdo Publishing, 2023)
Explore the world of insects, arachnids, centipedes, and millipedes with this illustrated encyclopedia of all things creepy-crawly.
Millipedes.
Includes bibliographical and online references (page 189) and index.
Keywords: Insects -- Encyclopedias, Juvenile; Arachnida -- Encyclopedias, Juvenile; Entomology -- Encyclopedias, Juvenile; Zoology -- Encyclopedias, Juvenile; Encyclopedias